New test of the Gabardine infiltration basin for mar in rio Seco (Campina da Faro aquifer system, Algarve) - Oliveira, M. M. (2015)
The infiltration basin constructed in the GABARDINE project in Rio Seco stream (Algarve, Portugal) was rehabilitated during MARSOL project and a new infiltration test has been performed. The hydrogeological framework is presented and the new infiltration test is described and interpreted. The results are similar to those obtained during GABARDINE project, with calculated infiltration rates varying with water height. When the infiltration basin is saturated and the water level is more than 0.16 m above the ground surface the infiltration rate raises to values of more than 1.19 m/day. The increasing rate of water level variation registered near the end of the filling stage of the infiltration basin indicates a lower porosity stratum that clues the presence of clogged stratum near the surface.